Optimalisasi Investasi Pendidikan untuk Pertumbuhan Ekonomi Berkelanjutan - Zakiah Nurul Fitri; Nanda Nur Hafizhah; Hasnah Hasnah; Hasna mustika Zahra; Ani Rahmaindah; Rafael Frizy Rajagukguk; Adif Nur Amanulloh; Fauzi Wiramadan; Ere Mardella Arbiani (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
Education has long been recognized as a primary determinant of economic progress and human development , yet in the context of a global economy characterized by rapid technological change and the sustainability imperative, the focus shifts from the mere quantity of investment to its effectiveness in fostering sustainable economic growth. Current education systems face significant challenges, including a persistent global "learning crisis" , governance inefficiencies , and a misalignment between curricula and the demands of the labor market, particularly the green and digital economies. Given that existing literature often treats education investment as a static input and fails to holistically integrate sustainability and governance into the optimization process , this conceptual article aims to bridge these theoretical and empirical gaps by proposing an integrated model for the optimization of education investment for sustainable economic growth. The method involves a conceptual analysis that synthesizes human capital theory , endogenous growth theory , and the economics of sustainability , emphasizing the roles of governance, innovation, and inclusivity as mediating factors. The key finding of the study indicates that optimization necessitates a paradigm shift from input-oriented budgeting toward an outcome-based investment framework that holistically balances three crucial dimensions: efficiency (maximizing learning outcomes) , equity (ensuring inclusive access) , and relevance (alignment with sustainability needs). The resulting policy implications are delineated across the Macro (fiscal integration and sustainability strategies through performance-based funding) , Meso (institutions transform into adaptive innovation centers) , and Micro (enhancement of reskilling, upskilling, and human capital capacity) levels; by achieving this alignment, education successfully transitions from a cost center to a strategic catalyst driving sustained prosperity.